The tales of Beedle the Bard - Rowling, J. K. (New York : Children's High Level Group in association with Arthur A. Levine Books, 2008)
Contains five illustrated moral tales for children from the world of Harry Potter, reportedly discovered and translated by young witch Hermione Granger, with an introduction and commentary from Albus Dumbledore, headmaster of Hogwarts School of Witchcraft and Wizardry.
The wizard and the hopping pot -- The Fountain of Fair Fortune -- The warlock's hairy heart -- Babbitty Rabbitty and her cackling stump -- The tale of the three brothers.
Wilson's Children, October 2010.
Wilson's Junior High School, January 2010.
School Library Journal, March 2009.
Booklist, January 2009.
Horn Book, March 2009.
Bulletin (Center for Children's books), March 2009.
Keywords: Wizards -- Juvenile fiction; Magic -- Juvenile fiction; Wizards -- Fiction; Magic -- Fiction; Fantasy; Short stories; Fantasy fiction; Fantasy fiction; Short stories